A Review Article on Selective Serotonin Reuptake Inhibitors (SSRIS) - Meena, Devi; Subhash Chand, Subhash; Kumar, Deovrat (Asian Journal of Pharmaceutical Research and Development, 2019)
Depression, tension and mental health have been ignored as a serious issue since ages. Depression can be fatal or life-threatening, if not treated to this problem. Antidepressants are also regularly used to treat many other conditions, such as social phobia, fibromyalgia, panic disorder, anxiety/anxiety depression, PTSD, OCD, PMDD, and menopause. The major antidepressant used in the study followed oral prescribing trends. A “serious adverse reaction means an adverse reaction which is fatal, life-threatening, disabling, incapacitating, or which results in or prolongs hospitalization.” Material method collect from Google, Wikipedia, Elsevier, PubMed, Google scholar, Sci-Hub etc. This is a meta-analysis study. Fluoxetine have the longest half-life, but Fluvoxamine have short half-life. SSRIs increase the serum concentrations of the latter two drugs, potentiating their effects and increasing the risk of toxicity. Fluoxetine and Paroxetine specifically, are known to cause a 5-fold increase in serum TCA concentration upon co-administration. By in the addition of combination therapy SSRIs associated many types of adverse drug reaction and some time it can cause serotonin syndrome also.